Characteristics and repair outcome of patients with Vesicovaginal fistula managed in Jimma University teaching Hospital, Ethiopia - Sori, Demisew Anemu (BMC Urol, 2016)
BACKGROUND: In Ethiopia, about 9000 fistula cases are estimated to occur every year with an incidence of 2.2/1000 women. This study was aimed to determine obstetric fistula characteristics and surgical repair outcomes among patients with fistula surgical repair. METHODS: A Hospital based cross sectional study design was conducted on all patients with Obstetric vesicovaginal Fistula, who were admitted to Gynecology ward, and had surgical repair from January 2011 to December 2014. Data was collected from patients’ chart, operation logbook and discharge logbook which were filled up from the entry of the patient to the hospital till her discharge. At discharge, a dye test was done to determine the outcome of repair. RESULTS: One hundred sixty eight patients with obstetric vesicovaginal fistula were repaired during the study period. The age of the women ranged from 12 to 45 years with mean of 25 (±6) years and 10.1 % were younger than 18 years. Eighty percent of patients were laboring for two or more days, 46.4 % delivered abdominally (cesarean section 24.4 %, hysterectomy for uterine rupture 22 %), and 85.7 % ended up in stillbirth. Most patients (56 %) had mid-vaginal vesicovaginal fistula. Route of repair was vaginal among 95.8 % of patients, and spinal anesthesia was applied among 70.8 % of patients. Out of 93.4 % patients who had successful closure of their fistula, 84.5 % of patients had their fistula healed and continent, 8.9 % of them developed urinary incontinence while 6.5 % of fistula repair had failed at the time of discharge. CONCLUSIONS: Most fistula patients in this study are older than 18 years, referred from health centers either for cephalopelvic disproportion or obstructed labor after prolonged labor at home. In this study, Spinal anesthesia as well as vaginal route was widely employed and high success rates were achieved with surgical repair. Therefore, increasing access to comprehensive emergency obstetric and new born care is essential to minimize the delay contributing to perinatal mortality and obstetric fistula. In addition use of spinal anesthesia and vaginal route of repair is essential for the high success of repair outcome and low postoperative morbidities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12894-016-0152-8) contains supplementary material, which is available to authorized users.